The Responsibility of Public Notary in Case of Ethical Code Violation - Syukron Sofwan; Amin Purnawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
This study aims to find out the responsibility of public notary and the legal consequence in case of ethical code violation by public notary. This research used empirical juridical method, with analytical descriptive research specification. The data have been analyzed qualitatively in describing the research problem. The result is done by taking the conclusion result deductively. The results of the research are: 1) the responsibility of public notary is obeying the ethical code. Ethical code is a moral guidance or direction for a particular profession or a list of responsibility in carrying out a profession composed by members of the profession itself and bidding them in practice. The punishment is organically applicable when the public notary violates professional ethical code as a guideline made by the professional organization. 2) the legal consequences in case of ethical code violation by public notary is a) in term of obedience, morality, and religion and based on conscience, it should be done by a public notary who holds and carries an honor position especially as a trustee. b) violations done by public notary against professional manner which have been recorded or regulated which have been arranged in written and binding and must be obeyed by all members of professional group and for those who violate the rules will get sanctions; c) the public notary who violates the ethical code as determined in legal constitution are accomplished based on the provision, so that the legal assurance of public notary’s profession are more guaranteed.Keywords: Responsibility; Public Notary; The Violation Of Ethical Code.